Effect of thyroidectomy in patients with tracheal compression - Koycegiz, Sinan; Mutlu, Vahit; Atalay, Fatma; Kars, Ayhan; Topal, Kubra; Yesilyurt, Mustafa (FapUNIFESP (SciELO), 2021)
Various therapeutic methods are employed to reduce thyroid gland compression of the trachea. Differences in the amount of shrinkage in the thyroid gland, in the amount of amelioration of tracheal compression, and in the amount of fibrosis after treatment may occur with these different methods. Although the compression of the trachea decreases after thyroidectomy, the number of studies showing the extent of this is limited. The purpose of this study was to investigate the effect of thyroidectomy performed due to tracheal compression, to reveal the extent of improvement using magnetic resonance imaging (MRI), and to evaluate our results.In total, 30 patients, i.e., 24 women and 6 men, with tracheal compression secondary to thyroid gland enlargement and undergoing total thyroidectomy were included in this study. MRI performed before surgery and 6 months after surgery. The amount of deviation from the tracheal midline and the tracheal lateral and anteroposterior (AP) diameters were measured, compared, and subjected to statistical analysis.Statistical analysis revealed significant differences between pre- and postoperative tracheal deviations, and lateral and AP diameters (p<0.001, p<0.001, and p=0.006, respectively). Histopathologically, benign or malignant pathology caused no significant difference in the postoperative improvement of tracheal anatomy (p=0.348 and p=0.148, respectively).Thyroidectomy performed due to tracheal compression provides significant improvement in tracheal anatomy. Due to its rapid and effective results, thyroidectomy should be one of the first options considered in the treatment of thyroid diseases with compression findings.
Keywords: Male; Trachea; Goiter; Tracheal stenosis; Thyroidectomy; Humans; Female; Thyroid Diseases; 3. Good health